Geodesic flow on elliptic paraboloid z=x^{2}+2y^{2} starting at (0,0). Geodesic flow on elliptic paraboloid z=x^{2}+2y^{2} starting at point away from (0,0). Geodesic flow on surface z=x^{4}+y^{4} starting at (0,0). Geodesic flow on surface z=x^{4}+y^{4} starting away at (0,0). Geodesic flow on surface z=x^{2}+y^{2} starting away at (0,0). Geodesic flow on surface z=x^{6}+y^{6} starting at (0,0). Geodesic flow on surface z=x^{6}+y^{6} starting away from (0,0). Geodesic flow on surface z=x^{2}+y^{2} - a (x^{4}+y^{4}) starting at (0,0). |